Effect of magnesium on the properties of LiNbO3 thin films prepared from polymeric precursors - Simoes, A. Z.; Gonzalez, A. H.; Riccardi, C. S.; Cilense, M.; Zaghete, M. A.; Stojanovic, B. D.; Tangastev, A.; Setter, N.; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2002)
The effect of magnesium addition on the phase formation, microstructure and electric and ferroelectric properties of LiNbO3 thin films prepared through polymeric precursors was analyzed. By X ray diffraction no secondary phase was observed with the increase of magnesium concentration. Comparing to pure LiNbO3, the addition of 0.5 and 1.0 mol% of Mg+2 increased of the dielectric constant, while 2.0 mol% decreased it. It was noticed that the increase in additive concentration decreases the ferroelectric remanent polarization and increases the coercive field.
Keywords: LiNbO3; thin films; electrical properties